A revised examination of the dual pathway model for bulimic symptoms: The importance of social comparisons made on Facebook and sociotropy. (December 2016) - Puccio, Francis; Kalathas, Fiona; Fuller-Tyszkiewicz, Matthew; Krug, Isabel
Abstract: Objective: To replicate the Dual Pathway Model (DPM) of bulimia nervosa (BN) symptoms prospectively, and to assess whether a revised version of the DPM that included the variables social comparisons made on Facebook and sociotropy influenced the DPM. Method: Participants were 245 females who completed baseline measures (T1) that assessed the DPM, as well as the constructs social comparisons made on Facebook, and sociotropy, and a follow-up questionnaire, which assessed symptoms of depression, bulimia, and dietary restraint, one month later (T2). Results: Path analysis revealed that the original and the revised DPMs had excellent fit once modifications to the respective models were made. In both DPMs, T1 pressures to be thin and T1 thin ideal internalization were related to T1 body dissatisfaction. T1 body dissatisfaction prospectively predicted T2 depressive symptoms and T2 bulimic symptoms, but not T2 dietary restraint. Furthermore, T2 dietary restraint, but not T2 depressive symptoms, predicted T2 BN symptoms. Results also showed that T2 dietary restraint was associated with T2 depressive symptoms. In the revised DPM, T1 social comparisons made on Facebook were associated with T1 body dissatisfaction, T1 pressures to be thin, and T2 bulimic symptoms. T1 sociotropy was related to T1 social comparisons on Facebook, T1 pressures to be thin, T1 body dissatisfaction, and T2 bulimic symptoms. Conclusions: Findings suggest the BN preventative efforts might benefit from addressing appropriate forms of social comparisons, especially those made on Facebook, and the personality trait sociotropy. Highlights: Limited support found for the dual-mechanism model proposed by the DPM. Sociotropy found to be a risk factor for BN symptoms. Appropriate Facebook use should be considered for bulimia prevention.